2023
DOI: 10.1038/s41598-022-27117-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor recalibration of postural control strategies occurs after whole body vibration

Abstract: Efficient postural control results from an effective interplay between sensory feedbacks integration and muscle modulation and can be affected by ageing and neuromuscular injuries. With this study, we investigated the effect of whole-body vibratory stimulation on postural control strategies employed to maintain an upright posture. We explored both physiological and posturography metrics, through corticomuscular and intramuscular coherence, and muscle networks analyses. The stimulation disrupts balance in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
(128 reference statements)
1
3
0
Order By: Relevance
“…Similar peaks are evident in primary orthostatic tremor and healthy controls when posture is perturbed 40 . A potential mechanism for this is an increased cortical drive to lower limb muscles, coupled with increased cortical activity in the beta band (15–30 Hz), as reported in experimentally induced imbalance in healthy controls 41 . Corticomuscular coherence studies also reported a shift towards cortical control in the 6–15 Hz and 16–40 Hz bands in healthy controls as the complexity of standing tasks increased 42 .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similar peaks are evident in primary orthostatic tremor and healthy controls when posture is perturbed 40 . A potential mechanism for this is an increased cortical drive to lower limb muscles, coupled with increased cortical activity in the beta band (15–30 Hz), as reported in experimentally induced imbalance in healthy controls 41 . Corticomuscular coherence studies also reported a shift towards cortical control in the 6–15 Hz and 16–40 Hz bands in healthy controls as the complexity of standing tasks increased 42 .…”
Section: Discussionsupporting
confidence: 57%
“…40 A potential mechanism for this is an increased cortical drive to lower limb muscles, coupled with increased cortical activity in the beta band (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), as reported in experimentally induced imbalance in healthy controls. 41 Corticomuscular coherence studies also reported a shift towards cortical control in the 6-15 Hz and 16-40 Hz bands in healthy controls as the complexity of standing tasks increased. 42 Taken together, these findings suggest that increased cortical drive in a high-frequency band may be an adaptive response to postural imbalance.…”
Section: Adaptive Mechanisms In Imbalancementioning
confidence: 97%
“…The range of such effects included both vibratory and acoustic stimulations ( 80 ) and direct effects on cortical structures using the transcranial direct current stimulation ( 81 ). It is interesting, according to some authors, WBV stimulation disrupts the body balance in the short term, but cortical activity may contribute to the formation of new synergies and modulation of muscle activity ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, whole-body vibration has been shown to contribute to a triggering towards recalibration of the sensorimotor systems. Rigoni et al found that when exposed to whole-body vibration, although the challenge destabilizes balance initially, the stimulation increases the recruitment of more muscular effort ( 29 ). It is postulated that this process shifts the muscle modulation towards a supraspinal control and recalibration of muscle recruitment ( 29 ).…”
Section: Discussionmentioning
confidence: 99%